#DoNotDisturb : how I ghosted my cell phone to take back my life - Bila, Jedediah (Harper, an imprint of HarperCollinsPublishers, 2018)
"The network and cable television personality shares her personal journey through the tumult of technology, in which she experiences the horrors and dangers of our smart-phone, social media, tech-polluted world, explores the reasons behind it, and reveals her ideas for reclaiming a real life in these virtual times. In this entertaining and inspiring book, Jedediah Bila chronicles her confusing, chaotic, and ultimately catastrophic love-hate relationship with her cell phone. Taking us through a series of what she calls her McFly Moments (named for the Back to the Future protagonist who sparked her simple life envy and desire to travel back to a seemingly easier time), Jedediah shares her most personal and embarrassing stories of mistakes made and sunsets missed, including the upending, life-altering months swirling in the digitally-enabled double life of her con man ex-boyfriend. Naming her affliction OCTD, (Obsessive Compulsive Tech Disorder) and heeding what she calls "the seven deadly signs that the tech apocalypse is upon us," Bila sets off to explore the consequences of too-much-tech, including: public cell-phone conversations as the second-hand smoke of the twenty-first century; Menage-a-Tech relationships; and the fact that we've all been programmed for addiction. Jedediah Bila applies the no-nonsense, common-sense, personal responsibility and accountability approach on which her television viewership, readers, and more than 400,000 social media followers have come to rely, to shout "Hey! My eyes are up here" and warn us all that if we don't start looking up to make eye contact with each other, our very humanity is at stake"--